2022
DOI: 10.1039/d2ta01011a
|View full text |Cite
|
Sign up to set email alerts
|

Helical PdPtAu nanowires bounded with high-index facets selectively switch the pathway of ethanol electrooxidation

Abstract: Intensive studies have been devoted to the preparation of electrocatalysts with outstanding activity and stability for ethanol oxidation. However, the electrocatalytic efficiency is far from satisfactory for application due to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…The current density of UNWs augments with increasing iridium atoms, which is in agreement with the previous report. 35 The mass activity of the Pt 43 Ir 32 Cu 25 UNWs is 1.05 A mg −1 , which is 1.3, 1.5, and 2.7 times higher than that 4,5 The enhanced electrocatalytic performance of UNWs can be ascribed to the synergistic effect of the alloy and the 1D nanostructures with high-density defect sites. As for breaking C−H and O−H bonds, Pt is considered to the best catalyst.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The current density of UNWs augments with increasing iridium atoms, which is in agreement with the previous report. 35 The mass activity of the Pt 43 Ir 32 Cu 25 UNWs is 1.05 A mg −1 , which is 1.3, 1.5, and 2.7 times higher than that 4,5 The enhanced electrocatalytic performance of UNWs can be ascribed to the synergistic effect of the alloy and the 1D nanostructures with high-density defect sites. As for breaking C−H and O−H bonds, Pt is considered to the best catalyst.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Many studies have shown that the EOR in the C 1 pathway, achieving maximum energy conversion, suffers from the slow reaction kinetics because the oxidation process involves the breaking of C–H and O–H bonds, splitting of the C–C bond in CH 3 CH 2 OH, and the poisoning of CO ads . , The enhanced electrocatalytic performance of UNWs can be ascribed to the synergistic effect of the alloy and the 1D nanostructures with high-density defect sites. As for breaking C–H and O–H bonds, Pt is considered to the best catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] At present, Pd-based nanomaterials are considered as one of the most effective EOR catalysts with excellent catalytic activity. [13][14][15][16][17][18][19] Nevertheless, the carbonaceous intermediates produced during the EOR will be adsorbed on the surface of Pd-based catalysts, which will reduce the catalytic performance. [20][21][22][23] Therefore, the development of durable Pd-based catalysts with high activity and efficiency is very important for the EOR.…”
Section: Introductionmentioning
confidence: 99%